BANKA HAVALESİ YOLUYLA GERÇEKLEŞEN İFADA ORTAYA ÇIKABİLECEK RİZİKOLARIN PAYLAŞILMASI - (:unkn) unknown (My University, 2017)
Banka havalesi havale ödeyicisinin bir banka olduğu her türlü havale olarak tanımlanabilir. Havale çoğu zaman ödeme aracı olarak borcunun ifası amacıyla kullanılır. Havale sürecine katılan banka ya da bankaların davranışları nedeniyle havale tutarı lehdarın hesabına zamanında ulaşmamış olabilir. Havale talimatında bir süre öngörülmemişse; bankanın objektif ölçülere göre, makul bir süre içinde ve kusurlu olarak gecikmeksizin havale talimatının gereğini yerine getirip getirmediği incelenecektir. Bu çalışmada havalenin gecikmesi ve gerçekleşmemesi durumunda sorumluluğun kimde olduğu incelenecektir

Bank wire transfer may be defined as any wire transfer where the wire payment would be made through a bank. Most of the time, a bank wire transfer is used as a method of payment for the performance of an obligation. Due to the bank(s)’s conduct involved in the transfer, a wire amount might not reach the creditor’s account on time. If there is no time frame provided in the wire transfer instructions, it will be examined whether the bank followed the wire transfer instructions within a reasonable time by objective standards, and without any undue delay. This paper examines who the responsible party is when the wire transfer is delayed or is not realized at all
(SHARING POSSIBLE RISKS THAT MIGHT EXIST DURING PERFORMANCE THROUGH A BANK WIRE TRANSFER)
Keywords: Hukuk